Identification of Fusarium and Aspergillus species from cornmeal in Malaysia and toxigenicity of mycotoxins produced - Perumal, Nithiyaa (2012)
Corn is a vital food source for human consumption, animal feed as well as industrial processing. However, corn faces repeated spoilage and contamination by a huge range of fungi especially by Fusarium and Aspergillus species. These fungi are known of producing mycotoxins such as fumonisins (FBs), moniliformin (MON), zearalenone (ZEA), beauvericin (BEA) and aflatoxins (AFs). Therefore the main objectives of this study were to identify and determine the diversity of Fusarium and Aspergillus species as well as to quantify the mycotoxins produced by both fungi associated with cornmeal in Malaysia. In this study, cornmeal samples were obtained from 9 states throughout Malaysia and the cornmeal samples were surface sterilized and cultured onto Peptone Pentachloronitrobenzene Agar (PPA) to isolate the fungi. Single spore isolation was carried out onto Potato Dextrose Agar (PDA) to obtain pure culture. Fusarium and Aspergillus isolates were selected and preceded with morphological identification. The diversity of Fusarium and Aspergillus species were determined using Shannon-Weiner index and this is followed by the extraction of mycotoxins. The extracted mycotoxins were analyzed qualitatively using Thin Layer Chromatography (TLC) and A. salina bioassay, and quantitatively using Ultra-fast Performance Liquid Chromatography (UFLC). A total of 314 isolates of microfungi were obtained, 90.5% isolates belonged to Aspergillus species, namely A. flavus (76.8%), A. niger (7.6%), A. nidulans (4.5%) and A. fumigatus (1.6%). Another 9.5% isolates were Fusarium species, identified as F. verticillioides (4.5%), F. semitectum (3.2%) and F. proliferatum (1.9%). As for the mycotoxin analysis, 15 out of 16 Fusarium isolates produced MON, 12 isolates produced BEA and all 16 isolates produced FB1. However none produced ZEA. In addition, 29 out of 40 Aspergillus isolates produced AFB1 and only two isolates produced AFB2. The analysis of A. salina revealed that all the five mycotoxins extracts were toxic to the brine shrimp despite the concentration of the mycotoxins. As a conclusion, a proper storage system for the corns should be implemented to avoid fungal contamination hence reducing the accumulation of mycotoxins.